Influence of chronic alcohol consumption on cerebral ischemia/reperfusion injury in female mice - Subedi, Utsab; Subedi, Pushpa; Rogers, Asia; Lu, Xiao-Hong; Panchatcharam, Manikandan; Sun, Hong (Frontiers in Cellular Neuroscience, 2025)
Light alcohol consumption (LAC) protects against cerebral ischemia/reperfusion (I/R) injury, whereas heavy alcohol consumption (HAC) worsens it in male mice. The phenomenon appeared to be associated with the dose-dependent influence of alcohol on cerebral angiogenesis and post-ischemic inflammation. However, whether there is a sex-specific difference is unknown. Therefore, the goal of this study was to examine the influence of chronic alcohol consumption on cerebral I/R injury in female mice. Female C57BL/6J mice were gavage-fed with 0.7 g/kg/day ethanol (designed as LAC), 2.8 g/kg/day ethanol (designed as HAC), or volume-matched water (designed as control) for 8 weeks. Subsequently, they were subjected to unilateral middle cerebral artery occlusion (MCAO) for 60 min. Under basal conditions, LAC reduced erythrocytes, whereas HAC reduced lymphocytes and monocytes. Neither LAC nor HAC affected exploratory behavior and memory performance, but both improved spontaneous motor activity and reduced anxiety. In addition, both LAC and HAC upregulated VEGFR2 and promoted cerebral angiogenesis. Furthermore, LAC upregulated TGF-β and TGF-βR2 and HAC upregulated VEGF-A. Following MCAO, LAC significantly reduced cerebral I/R injury, blood-brain barrier (BBB) disruption, neutrophil infiltration, and microglial activation and increased cerebral angiogenesis at 72 h of reperfusion. In contrast, although HAC reduced BBB disruption and neutrophil infiltration, it did not significantly alter cerebral I/R injury, post-ischemic cerebral angiogenesis, or microglial activation. Our findings suggest that LAC protects against transient focal cerebral ischemia in female mice. The beneficial effect may be related to its pro-angiogenic and anti-inflammatory properties.